2016
DOI: 10.1016/j.neuroimage.2016.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of global interference of scalp-hemodynamics in functional near-infrared spectroscopy using short distance probes

Abstract: Functional near-infrared spectroscopy (fNIRS) is used to measure cerebral activity because it is simple and portable. However, scalp-hemodynamics often contaminates fNIRS signals, leading to detection of cortical activity in regions that are actually inactive. Methods for removing these artifacts using standard source-detector distance channels (Long-channel) tend to over-estimate the artifacts, while methods using additional short source-detector distance channels (Short-channel) require numerous probes to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
176
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 132 publications
(182 citation statements)
references
References 66 publications
5
176
1
Order By: Relevance
“…Here we showed that our method using just a few short distance probe channels (Short-channels) [9] can be used for scalp artifact removal during motor learning tasks. Nevertheless, several different artifact removal methods have been proposed so far [2].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…Here we showed that our method using just a few short distance probe channels (Short-channels) [9] can be used for scalp artifact removal during motor learning tasks. Nevertheless, several different artifact removal methods have been proposed so far [2].…”
Section: Discussionmentioning
confidence: 91%
“…In cases applying the removal we used a method to incorporate scalp hemodynamic components into the model, referred to as ShortPCA [9]. In this method, the equation used for the analysis of fNIRS Long-channel in each trial is as follows:…”
Section: Fnirs Analysismentioning
confidence: 99%
See 3 more Smart Citations